INCLUSION OF HUMAN CAPITAL IN THE CALCULATION OF WACC - Sujata Priyambada Dash; Vijay Agrawal; Avinash Sinha (European Scientific Journal, ESJ, 2013)
Economic Value Added (EVA) is very weak in the Indian business organization. The acceptance level is very low rather popularity of its theoretical aspects. The researcher has found that there is a gap in the study of acceptance level of human capital relations to contemporary financial analysis EVA in the Indian context. The study has attempted to focus on the performance of the organization through human capital which contributes as well enhance Economic Value Addition of the organization. EVA is a financial performance metric that measures value based on adjusted accounting data to assess financial performance and help a company grow. (Stewart, p.3; Makelainen and Rozticki, 1998, p.7) Economic Value Added measures the profitability of a company after taking into account the cost of all capital including equity. It is the post-tax return on capital employed (adjusted for the tax shield on debt) minus the cost of capital employed.The dichotomy in accounting between human and non-human capital is fundamental. The latter is recognized as an asset and is therefore recorded in the books and reported in the financial statements, whereas the former is ignored by accountants. The definition of wealth as a source of income inevitably leads to the recognition of human capital as one of the several forms of wealth such as money, securities and financial capital. The study found that it is very difficult to measure human capital in Indian organization due to different HR practices in different organization depending upon the size and nature of the business.It is difficult to calculate the cost of capital including human capital, so the organizations face limitation to keep the record in measuring human capital and return on human capital in value-added financial statement (EVA) in quantitative terms. Although the organizations in European countries, USA and China have quantified the Return on Investment (ROI) through human capital and thereby found out the true economic profit of the organizations ﻿assumed as performance measurement and reflects in value –added financial statements; Economic Value Addition.However, in Indian context, there are organizations that have used Lev and Schwartz model to validate human capital. But, majority of manufacturing and service industries have not yet perceived that the assessment of economic value addition is possible through measurement of human capital.After an exhaustive literature survey, the paper will discuss the intertwined concepts of EVA and human capital. The paper first has explored the definitions of human capital cited by different researchers and also has attempted to find out the impact of EVA of the organization after incorporating cost of human capital in the Weighted Average Cost of Capital (WACC).